2007
DOI: 10.2118/97886-pa
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Heavy-Oil Emulsions

Abstract: Summary Water is invariably produced with crude oil. If there is enough shear force when crude oil and produced water flow through the production path, stable emulsions may be formed. This scenario may particularly be present during the production of heavy oils, where steam is used to reduce the viscosity of heavy oil, or in cases in which submersible pumps are used to artificially lift the produced fluids. To efficiently design and operate heavy-oil production systems, knowledge of the reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…W/O emulsions must be treated to remove the associated water and inorganic salts, to obtain oil with proper specifications for transport, storage and exportation and to reduce the corrosion and contamination of catalyzers at processing plants. 1,2 W/O emulsions are stabilized by emulsifiers (surfactants), which tend to migrate and concentrate at the W/O interface, forming a film that reduces the interfacial tension between the phases, promoting the dispersion of water droplets in the continuous phase and inhibiting their coalescence. Some natural emulsifiers are present in crude oil, such as asphaltenes, resins and organic acids and bases.…”
Section: Introductionmentioning
confidence: 99%
“…W/O emulsions must be treated to remove the associated water and inorganic salts, to obtain oil with proper specifications for transport, storage and exportation and to reduce the corrosion and contamination of catalyzers at processing plants. 1,2 W/O emulsions are stabilized by emulsifiers (surfactants), which tend to migrate and concentrate at the W/O interface, forming a film that reduces the interfacial tension between the phases, promoting the dispersion of water droplets in the continuous phase and inhibiting their coalescence. Some natural emulsifiers are present in crude oil, such as asphaltenes, resins and organic acids and bases.…”
Section: Introductionmentioning
confidence: 99%
“…In the present chapter, we concluded from the Herschel-Bulky model that the water-in-crude oil emulsion for light type of crude oil emulsion at temperature ranges from 20 to 90°C is a dilatant non-Newtonian type since the flow behavior index is greater than 1. On the contrary, it has been reported earlier by Alboudwarej et al [12] that a heavy type of crude oil emulsion demonstrated both Newtonian and non-Newtonian behaviors at temperature ranges from 20 to 70°C. They highlighted that the oilfield emulsions have formed several different morphologies (water/oil emulsion (W/O), oil/water/oil emulsion (O/W/O), double water/oil/water emulsion (W/W/O/W) and others).…”
Section: Rheological Model Of Light Crude Oil Emulsionmentioning
confidence: 70%
“…They highlighted that the oilfield emulsions have formed several different morphologies (water/oil emulsion (W/O), oil/water/oil emulsion (O/W/O), double water/oil/water emulsion (W/W/O/W) and others). The difference in morphology hence produced structural diversity and was postulated by Alboudwarej et al [12] causing the scatter of the rheological properties of oilfield emulsion from Newtonian to non-Newtonian. To characterize quantitatively the scatter rheological properties, we determined the rheological behavior of the oilfield emulsion as a function of temperature.…”
Section: Rheological Model Of Light Crude Oil Emulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emulsions that are used in practice normally contain an emulsifying agent (surfactant). [1][2][3][4][5] Emulsions are normally divided into two groups, namely water-in-oil or oil-in-water emulsions. Water-in-oil emulsions may be encountered at all stages in the petroleum industry such as drilling fluids, production, and transportation.…”
Section: Introductionmentioning
confidence: 99%